Unraveling the physical properties of Mn-doped CdS diluted magnetic semiconductor quantum dots for potential application in quantum spintronics - Maity P.; Kumar R.; Jha S.N.; Bhattacharyya D.; Singh R.K.; Chatterjee S.; Ghosh A.K. (My University, 2025)
The tunability of structural, optical, electronic, and magnetic properties in semiconductor quantum dots (QDs) makes them promising materials for multiple spintronic and optoelectronic applications. ﻿However, controlling the size of QDs to tune these properties is challenging due to their quantum size and high sensitivity to the ambient atmosphere. Here, we demonstrate successfully synthesized tunable Mn-doped cadmium sulfide (0% ≤ Mn ≤ 6%) diluted magnetic semiconductor QDs by hot injection chemical route. XRD and TEM studies confirmed that undoped and Mn-doped CdS QDs are polycrystalline in cubic phase without having any dopant-related signature. The XPS study shows the spin–orbit split due to Mn-doping and the atomic percentage of each element present in the prepared sample has been calculated from XPS data. XANES (X-ray Absorption Near Edge Structure) study shows that the Cd has the same oxidation state (+2) in the undoped and Mn-doped CdS QDs and also Mn has +2 oxidation state in Mn-doped CdS QDs. Extended X-ray Absorption Fine Structure (EXAFS) measurements show local structural disorder in higher doping concentration of Mn. It also shows that due to Mn doping, the coordination number of S in all the Mn-doped samples have the S vacancy compared to undoped CdS. No significant change has been observed in FTIR spectra after Mn doping. Raman spectra exhibits two longitudinal optical (LO) modes at 299 cm−1 and 598 cm−1. The intensity of the first LO peak decreases rapidly and linearly due to local structural and short-range disorder induced with increasing Mn concentration in CdS. UV–Vis spectroscopy reveals non-linear variation of bandgap energy showing the downwards bowing with increasing Mn-doping concentration. PL and TRPL indicate appearance of surface defect states with Mn-doping. TRPL spectra show decrease in decay time due to Mn‐doping. Room temperature ferromagnetism of Mn-doped CdS QDs confirms the diluted magnetic semiconductor behavior, which would play key role in quantum spintronics. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.